Strategic Leadership in the Business School : Keeping One Step Ahead / [electronic resource] - Fragueiro, Fernando; Thomas, Howard (Cambridge : Cambridge University Press, 2011)
Business schools have come under fire in recent years with criticisms centring on their academic rigour and the relevance of business education to the 'real' world of management. Alongside this ongoing debate, increasing international competition and media rankings have led to a fierce struggle between business schools for positioning and differentiation. These are among the challenges that are faced by the Dean of the modern-day business school. In this book, Fernando Fragueiro and Howard Thomas show how Deans of business schools can meet such challenges in terms of strategic direction setting and the execution of their leadership role. Drawing on their invaluable experience as Deans of highly successful business schools, they present a series of case studies to show how leaders of five leading business schools (IMD, LBS, INSEAD, IAE and Warwick) have built effective strategies in the context of internal and external political pressures.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).